2011
DOI: 10.1186/1471-2458-11-924
|View full text |Cite
|
Sign up to set email alerts
|

Fatal alcohol intoxication in women: A forensic autopsy study from Slovakia

Abstract: BackgroundPlenty of information related to alcoholism can be found in the literature, however, the studies have mostly dealt with the predominance of male alcoholism and data related to addiction in women are desperately scarce and difficult to find. Basic demographic data focusing on the impact of acute alcohol intoxication on the circumstances of death and social behaviour in the alcohol addicted female population are needed especially in the prevention of alcohol related mortality.MethodsA retrospective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A study in Slovakia showed that death due to acute alcohol poisoning (AAP) accounts for a significant proportion of all deaths related to alcohol consumption [ 10 ]. Similar results have been found in women [ 11 ]. Death due to AAP is a serious consequence of heavy drinking.…”
Section: Introductionsupporting
confidence: 91%
“…A study in Slovakia showed that death due to acute alcohol poisoning (AAP) accounts for a significant proportion of all deaths related to alcohol consumption [ 10 ]. Similar results have been found in women [ 11 ]. Death due to AAP is a serious consequence of heavy drinking.…”
Section: Introductionsupporting
confidence: 91%
“…In our autopsy case, we interestingly did not identify the typical risk factors for black esophagus which are mentioned in the literature such as age, male gender, underlying organic disease, severe alcohol consumption, etc. (5,7,9,12,29,30). To the best of our knowledge, this is the first reported case of acute esophageal necrosis in association with combined intoxication with three various types of antipsychotics.…”
Section: Discussionmentioning
confidence: 92%
“…Articles reported young, middle, and old “age” to identify hardly reached individuals. In the category “sex,” each of male and female were used to identify individuals as hardly reached (Straka et al, 2011; Vandelanotte et al, 2013). Within the six categories in the cultural and environmental domain, “social network” included both low and high social support (Nelson et al, 2012; Riggs et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Older adults were hardly reached due to limited mobility and access to health services (Hinrichs et al, 2011). Sex was associated with reach based upon power relations—advantage to males and/or expected gender roles—females more likely to participate (Straka et al, 2011; Vandelanotte et al, 2013). What attributes cause interventions to fail to reach their intended audiences clearly depend on multiple factors surrounding the interventions and their audiences.…”
Section: Discussionmentioning
confidence: 99%